(untitled) (Journal of Pharma Insights and Research, 2025)
The muscle relaxant potential of Matricaria chamomilla (chamomile) was evaluated using rotarod apparatus in experimental mice models. Fresh leaves of M. chamomilla were collected from Karimnagar, Telangana, India, and subjected to methanolic extraction after petroleum ether treatment. Phytochemical tests have the presence of flavonoids, cardiac glycosides, saponins, tannins, and alkaloids. The muscle relaxant activity was evaluated using albino mice (20-35g) divided into four groups: acute toxicity, control, test drug, and standard drug (diazepam) groups. The methanolic extract showed 16% w/w yield and showed significant muscle relaxant effects at 200 mg/kg body weight. The fall-off time for control group animals ranged from 40-151 seconds, while the test group administered with plant extract showed fall-off times between 45-180 seconds. The standard drug diazepam (4 mg/kg) group showed fall-off times of 20-45 seconds. The muscle relaxant effects were attributed to bioactive compounds, particularly flavonoids like apigenin, which potentially interact with benzodiazepine receptors. The study confirmed the safety profile of chamomile extract at the tested dose and validated its traditional use as a muscle relaxant through scientific evaluation.